(untitled) (The Review of Diabetic Studies, 2025)
Saudi Arabia’s Vision 2030 healthcare transformation framework necessitates comprehensive examination of cross-disciplinary collaboration among healthcare technicians operating within modern hospital ecosystems. This review examines the synergistic integration of midwifery, nursing, health informatics, radiology, pharmacy, and health administration technicians within Saudi Arabian healthcare delivery systems. Through systematic analysis of peer-reviewed literature published between 2016 and 2024, this study synthesizes evidence regarding interprofessional collaboration frameworks, technology-enabled care coordination, and workforce development initiatives aligned with national health transformation objectives. Findings reveal that effective cross-disciplinary integration requires structured communication protocols, shared digital health platforms, competency-based training programs, and organizational cultures that facilitate knowledge exchange across professional boundaries. The Saudi healthcare system demonstrates progressive adoption of integrated care models, though persistent challenges include standardization of interprofessional education, optimization of health information technology infrastructure, and alignment of regulatory frameworks across diverse technical specialties. This review contributes theoretical understanding of sociotechnical systems theory application within Middle Eastern healthcare contexts and provides evidence-based recommendations for strengthening collaborative practice models. Future research should prioritize longitudinal evaluation of interprofessional interventions and patient outcome measures within Saudi hospital settings.